Evaluating systematic reanalysis of clinical genomic data in rare disease from single center experience and literature review. Issue 11 (23rd September 2020) - Tan, Natalie B.; Stapleton, Rachel; Stark, Zornitza; Delatycki, Martin B.; Yeung, Alison; Hunter, Matthew F.; Amor, David J.; Brown, Natasha J.; Stutterd, Chloe A.; McGillivray, George; Yap, Patrick; Regan, Matthew; et al.
Abstract: Background: Our primary aim was to evaluate the systematic reanalysis of singleton exome sequencing (ES) data for unsolved cases referred for any indication. A secondary objective was to undertake a literature review of studies examining the reanalysis of genomic data from unsolved cases. Methods: We examined data from 58 unsolved cases referred between June 2016 and March 2017. First reanalysis at 4–13 months after the initial report considered genes newly associated with disease since the original analysis; second reanalysis at 9–18 months considered all disease‐associated genes. At 25–34 months we reviewed all cases and the strategies which solved them. Results: Reanalysis of existing ES data alone at two timepoints did not yield new diagnoses. Over the same timeframe, 10 new diagnoses were obtained (17%) from additional strategies, such as microarray detection of copy number variation, repeat sequencing to improve coverage, and trio sequencing. Twenty‐seven peer‐reviewed articles were identified on the literature review, with a median new diagnosis rate via reanalysis of 15% and median reanalysis timeframe of 22 months. Conclusion: Our findings suggest that an interval of greater than 18 months from the original report may be optimal for reanalysis. We also recommend a multi‐faceted strategy for cases remaining unsolved after singleton ES. Abstract : We evaluated the systematic reanalysis of singleton exome sequencing (ES) data for unsolved cases and undertook a literature review of studies examining reanalysis of genomic data from unsolved cases. Our findings suggest that an interval of greater than 18 months from the original report may be optimal for reanalysis. We also recommend a multi‐faceted strategy for cases remaining unsolved after singleton ES.